INTERCULTURAL INTERACTION IN THE CONTEXT OF RELIGIOUS COMMUNICATION: A SOCIO-PHILOSOPHICAL ASPECT - Sidorkina, Olena (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Over the past decade, intensified global migration has created pressing economic, political, cultural, and psychological challenges. As both a product and driver of globalization, migration fosters sustained contact between diverse cultural traditions, reshaping intercultural interaction. Religious communication, as a marker of civilizational identity, plays a key role in this process. Addressing its consequences requires socio-philosophical reflection to develop communication-based approaches to mitigating negative effects. The aim of this article is to study the peculiarities of intercultural interaction in the context of religious communication in the face of socio-cultural challenges in today's information society. Research methods. The study is based on the core principles of the dialectical approach, socio-cultural determinism, systems theory, communicative philosophy, and the axiological foundations of communicative interaction, as well as elements of phenomenology. The generalisations presented also draw on philosophical research into communicative discourse in contemporary society. Research results. One of the socio-philosophical aspects of the religious and communicative component of intercultural interaction is the analysis of how culturally significant centres and zones of social contact are shifting from historically established territorial spaces to the virtual realm of information networks under the influence of information and communication globalisation— a process that dialectically leads to transformations in the real territorial space of intercultural interaction, often taking the form of cultural intrusions or invasions. Discussion. In today’s information society, the internationalisation of cultural and economic relations fosters both secularising and unifying tendencies, alongside a revival of traditionalism in the form of demonstrative religiosity. Despite the rise of rationalism and pragmatism, the religious dimension of communication persists, often intertwining with rationality and taking on new, sometimes politicised forms. To overcome negative trends in intercultural interaction, the globalisation model is increasingly giving way to dialogue as a modern form of internationalisation. Conclusions. Intercultural interaction in the context of religious communication in the information society reflects the dichotomy between the global (cosmopolitan) and the local (national, traditional), expressed in conflicting processes of adaptation and enclavisation, dialogue and confrontation. The religious and communicative dimension manifests in the shift of cultural interaction centres from traditional territorial spaces to virtual information networks, which also influences real territorial interaction. To counter negative trends, a shift towards dialogue is essential as a modern form of internationalising social and communicative relations